The Effect of Al-Qur'an Murottal Therapy Surah Ar-Rahman on Reducing Blood Pressure in Menopausal Women Suffering from Hypertension in Purwakarta Regency, Indonesia - Humaeroh, Dita (Journal of Anesthesiology and Clinical Research, 2024)
Background: Hypertension is a chronic disease that often occurs in menopausal women. Murottal therapy from Al-Qur'an Surah Ar-Rahman is believed to lower blood pressure. This study aims to determine the effectiveness of murottal therapy from Al-Qur'an Surah Ar-Rahman on reducing blood pressure in menopausal women with hypertension in Purwakarta Regency, Indonesia. Methods: This research used a quasi-experimental design with a pretest-posttest with a control group design. A total of 60 menopausal women with hypertension in Purwakarta Regency were randomly divided into two groups: the intervention group (n=30) who received murottal therapy of Al-Qur'an Surah Ar-Rahman for 30 minutes every day and the control group (n=30) who did not receive the intervention. Blood pressure was measured before and after intervention for 4 weeks. Results: The results showed that there was a significant difference in the reduction in systolic and diastolic blood pressure between the intervention and control groups after 4 weeks (p<0.05). Systolic blood pressure in the intervention group fell by an average of 10.5 mmHg, while in the control group, it fell by an average of 3.2 mmHg. Diastolic blood pressure in the intervention group fell by an average of 7.4 mmHg, while in the control group it fell by an average of 2.8 mmHg. Conclusion: Al-Qur'an murottal therapy Surah Ar-Rahman is effective in lowering blood pressure in menopausal women with hypertension.